Effect of Prostate Artery Embolization on Erectile Function – A Single Center Experience of 167 Patients. Issue 4 (17th February 2022) - Bhatia, Shivank; Acharya, Vedant; Jalaeian, Hamed; Kumar, Jessica; Bryant, Evan; Richardson, Andrew; Malkova, Kseniia; Harward, Sardis; Sinha, Vishal; Kably, Issam; Kava, Bruce R.
ABSTRACT: Background: Prostate artery embolization (PAE) is an emerging therapy for lower urinary tract symptoms (LUTS) associated with benign prostatic hyperplasia (BPH). Aim: This retrospective study was conducted to assess the effect of prostate artery embolization (PAE) on erectile function in a cohort of patients with LUTS attributable to BPH at 3-months after the procedure. Methods: A retrospective review was performed on 167 patients who underwent PAE. Data collected included Sexual Health Inventory in Men (SHIM) scores at 3, 6, and 12 months post-PAE, in conjunction with the International Prostate Symptom Scores (IPSS), Quality of Life (QoL) scores, and prostate volumes. Primary outcome was erectile function as assessed by SHIM scores at 3 months after PAE. An analysis was performed to identify patients with a ±5-point SHIM change to group them according to this minimum clinically significant difference in erectile function. Adverse events were recorded using the Clavien-Dindo (CD) classification. Outcomes: At 3 months following PAE, median IPSS decreased by 16.0 [IQR, 9.0–22.0] points, median QOL decreased by 4.0 [IQR, 2.0–5.0] points, and median prostate volume decreased by 33 g [IQR, 14–55]. Results: Median SHIM score was 17.0 [IQR, 12.0–22.0] at baseline, 18.0 [IQR, 14.0–23.0] at 3 months [ P = .031], 19.0 [IQR, 14.5–21.5] at 6 months [ P = .106] and 20 [IQR, 16.0–24.0] at 12 months [ P = .010] following PAE. In patients with no erectile dysfunction (ED) at baseline, 21% (n = 9) reported some degree of decline in erectile function post-PAE. However, 38% (n = 40) of patients who presented with mild-to-moderate ED reported improvement in their erectile function 3 months following PAE. Overall, the changes in baseline SHIM score were relatively small; 82% (n = 137) of patients did not have more than 5 points of change in their SHIM scores at 3 months following PAE. Clinical Implications: Our findings suggest PAE has no adverse impact on erectile function for most patients. Strengths & Limitations: The study was performed at a single center with 1 operator's experience, and is retrospective with no control group. Conclusion: Findings suggest that prostate artery embolization has no adverse effect on erectile function in the majority of patients with LUTS attributable to BPH at 3 months after the procedure.